Cramps frequency and severity are correlated with small and large nerve fiber measures in type 1 diabetes. Issue 1 (January 2018) - Abraham, Alon; Barnett, Carolina; Lovblom, Leif E.; Perkins, Bruce A.; Bril, Vera; Katzberg, Hans D.
Highlights: Muscle cramps are very common, especially in type 2 diabetic polyneuropathy. Muscle cramps correlate with small and large nerve fiber measures in type 1 diabetes. Muscle cramp frequency and severity also correlate with conduction velocities in type 1 diabetes. Abstract: Objectives: To explore the correlations between different muscle cramp characteristics including cramp frequency and severity and clinical and large and small nerve fiber measures in patients with diabetes type 1 (DM 1) and 2 (DM 2). Methods: Prospective cross sectional study of healthy controls and patients with DM 1 and DM 2 recruited between April 2009 and November 2012. Participants underwent clinical evaluation and large and small nerve fiber studies, and the frequency and correlations of muscle cramps were explored. Results: 37 controls, 51 patients with DM 1, and 69 patients with DM 2 were studied. Muscle cramps were the most frequent symptom captured by the Toronto Clinical Neuropathy Score (TCNS) in all groups, up to 78% in patients with DM 2. In patients with DM 1, but not DM 2, muscle cramp frequency and severity were correlated with clinical (TCNS) and both large (electrophysiology and vibration perception thresholds) and small nerve fiber measures. Conclusions: Muscle cramps are frequent in diabetes and are correlated with clinical and both small and large nerve fiber measures in DM 1, suggesting that their origin and propagation might extend beyond the motor nerve. Significance: Muscle cramps correlate with nerve fiber measures in DM 1.